Dynamics and control of robotic manipulators with contact and friction - Liu, Shiping, 1971-; Chen, Gang (Mechanical engineer) (Wiley, 2019)
"Self-contained and comprehensive reference with systematic treatment and a unified framework - Simulation and experiments are both used in dynamics and control of robot considering contact, impact and friction - Discusses latest tribology methodology to treat the multiple ?scale effects - Description of experiments and software used - Detailed account on the methods to handle friction in the closed loop, including the principles, implementation, application scope, the merits and demerits - Unified treatment covering tribology and multi-scales, multi-physics, nonlinear stochastic dynamics control Market description: Primary market: Senior undergraduate, graduate students of robotics, mechatronics, mechanical engineering, tracking control. Secondary market: Practicing professionals and industrial researchers"--